A new electrode design for ambipolar injection in organic semiconductors. Issue 1 (December 2017) - Kanagasekaran, Thangavel; Shimotani, Hidekazu; Shimizu, Ryota; Hitosugi, Taro; Tanigaki, Katsumi
Abstract Organic semiconductors have attracted much attention for low-cost, flexible and human-friendly optoelectronics. However, achieving high electron-injection efficiency is difficult from air-stable electrodes and cannot be equivalent to that of holes. Here, we present a novel concept of electrode composed of a bilayer of tetratetracontane (TTC) and polycrystalline organic semiconductors (pc-OSC) covered by a metal layer. Field-effect transistors of single-crystal organic semiconductors with the new electrodes of M/pc-OSC/TTC (M: Ca or Au) show both highly efficient electron and hole injection. Contact resistance for electron injection from Au/pc-OSC/TTC and hole injection from Ca/pc-OSC/TTC are comparable to those for electron injection from Ca and hole injection from Au, respectively. Furthermore, the highest field-effect mobilities of holes (22 cm2 V–1 s–1 ) and electrons (5.0 cm2 V–1 s–1 ) are observed in rubrene among field-effect transistors with electrodes so far proposed by employing Ca/pc-OSC/TTC and Au/pc-OSC/TTC electrodes for electron and hole injection, respectively. One of technological challenges building organic electronics is efficient injection of electrons at metal-semiconductor interfaces compared to that of holes. The authors show an air-stable electrode design with induced gap states, which support Fermi level pinning and thus ambipolar carrier injection.